Improving energy efficiency of monomer production units through direct process integration; E3S Web of Conferences; Vol. 541 : VI International Scientific Forum on Computer and Energy Sciences (WFCES 2024) - Gil T. A. Tatjyana Alekseevna (Renewable Energy Sources and Energy-Saving Technologies, 2024)
Title screen